The Pillars of Hajj for Muslims and Their Impact on The Pilgrim - Jabbar, Hadee Radhi (Syura: Journal of Law, 2025)
This study investigates the multifaceted dimensions of Hajj, the Islamic pilgrimage, which is not only a fundamental religious obligation but also a transformative spiritual journey with deep personal and communal significance. While Hajj is well-established in Islamic jurisprudence as one of the five pillars of Islam, this research identifies a gap in understanding its broader impacts beyond the legal framework. The primary aim of this study is to analyze the educational, spiritual, social, and psychological effects of Hajj, particularly among Iraqi pilgrims. Employing a qualitative analytical method, the study draws upon classical Islamic sources, contemporary literature, and testimonies from Iraqi pilgrims to explore the lived experience of Hajj. The findings are organized into four thematic dimensions. The first addresses the legal foundation of Hajj, including its legitimacy, types, and essential rulings. The second highlights the spiritual and moral impacts, such as enhanced self-discipline, deeper faith, and increased humility. The third focuses on social and cultural benefits, including the promotion of Muslim unity, intergroup tolerance, and the sharing of diverse experiences. The fourth examines psychological effects, such as emotional healing, inner peace, and the profound feeling of divine connection and repentance. This research concludes that Hajj transcends its ritualistic form to become a life-changing experience that reshapes a believer’s relationship with God, self, and society. The study contributes to Islamic studies by offering a holistic understanding of Hajj’s role in individual transformation and communal harmony, especially within the context of Iraqi society.